Improving Innovation Performance by Convergence in Open Innovation: Evidence from Software Firms in Sri Lanka - Yapa, S.R.; Senathiraja, R; Kauranen, I (Faculty of Management Studies and Commerce, University of Sri Jayewardenepura, 2018)
Open innovation, which encourages firms to use external knowledge and external partners to accelerate innovation, has become a popular approach among organisations globally. Researchers have highlighted multiple benefits that open innovation offers. Extant literature often discusses factors of open innovation that increase innovation performance. However, open innovation does not always bring higher innovation performance and reasons for this are not adequately addressed in the existing literature. The objective of this research study is to increase understanding of factors that can hinder innovation performance in open innovation implementations. Special attention has given to convergence. In this case, convergence refers to alignment and coordination between innovation partner firms. The empirical data for this research study will be gathered from software firms in Sri Lanka. The background for this study is the software firms in Sri Lanka which have not reached the expectation that have been placed on them.